Ag2O/sodium alginate supramolecular hydrogel as a film photocatalyst for removal of organic dyes in wastewater. Issue 25 (7th March 2017) - Ma, Yuhua; Wang, Jiajia; Xu, Shimei; Zheng, Zhendong; Du, Juan; Feng, Shun; Wang, Jide
Abstract : As a film photocatalyst, a Ag2 O/sodium alginate supramolecular hydrogel exhibited excellent photocatalytic degradability, great adsorptivity, highly efficient charge separation and reusability. Abstract : A simple method was proposed to fabricate a Ag2 O supported alginate supramolecular hydrogel film using solution casting technology. The photocatalytic degradability of the film was investigated with methylene blue and malachite green as model dyes. Under irradiation of either UV or visible light, the photodegradation rates were above 93% for both dyes with relatively short degradation times. The film exhibited great adsorptivity of dyes (∼76%), highly efficient charge separation and reusability (∼90% of its initial activity after five runs). Furthermore, the potential photocatalytic mechanism was explored for the degradation of MB and MG with the film under visible light irradiation. This work provides a new insight into the fabrication of supramolecular hydrogel films as highly efficient photocatalysts for wastewater treatment in practice.